ANALISIS KEJADIAN KEGAWATDARURATAN MATERNAL DI RUMAH SAKIT DR. PP MAGRETTY KABUPATEN KEPULAUAN TANIMBAR - Kasmiati; Arvicha Fausiah; Jakob L. Jambormias (Journal of Innovation Research and Knowledge, 2025)
An emergency is an unexpected, dangerous event that occurs suddenly and is life-threatening which will lead to death. The maternal mortality rate is still a health problem that cannot be reduced in Indonesia. The DR. PP Magretty Hospital, Tanimbar Islands Regency, is the only hospital in the Tanimbar Islands Regency which is a referral place for the 13 Community Health Centers in the Tanimbar Islands Regency. The research aims to analyze the incidence of maternal emergencies. This research uses a descriptive method by obtaining retrospective data from the medical records of patients who experienced maternal emergencies at the DR. PP Magretty Hospital, Tanimbar Islands Regency. The population of this study was pregnant, labor, postpartum, and who experienced emergencies in January – December 2022, while the sampling technique was total sampling. The research results showed that the highest cases of maternal emergencies were Preeclampsia/eclampsia 42 (17.87%) cases, Abortion 42 (17.87%) cases, Intrauterine Fetal Death (IUFD) 36 (15.31%) cases, Hyperemesis Gravidarum 19 Cases (8.08%), long second stage 19 (8.08%) cases, premature rupture of membranes (PROM) 18 (7.65%) cases, retained placenta 17 (7.23%) cases, placenta previa 11 ( 4.68%) cases, Postpartum Hemorrhage (PPH) 9 (3.82%) cases, Old First Stage 8 (3.40%) cases, Disturbed Ectopic Pregnancy 5 (2.12%) cases, Uterine atony 4 ( 1.70%) cases, Serotinus 3 (1.27%) cases, Uterine Rupture 2 (0.85%) cases. In conclusion, it is hoped that this maternal emergency case can be prevented from occurring by carrying out early detection and carrying out appropriate and fast treatment and referral.